Delays to the diagnosis of cervical dystonia. (March 2016) - Bertram, Kelly L.; Williams, David R.
Abstract: The diagnosis of cervical dystonia (CD) is based on physical examination and is therefore reliant on clinician experience. Due to variability of presenting symptoms it may be misdiagnosed, thus delaying the provision of effective treatment. We sought to determine the average time taken to make a diagnosis of CD in our clinical cohort and explore contributing factors to diagnostic delay. Forty-nine patients with a diagnosis of CD attending a movement disorder specialist for treatment completed a questionnaire regarding symptoms and clinical interactions at onset and diagnosis. The mean time from symptom onset to diagnosis was 6.8 years (range 0–53 years). More than 50% of patients sought physical therapies initially, prior to consulting their general practitioner. Only 40% of patients sought medical advice within the first 6 months of symptom onset and only 10% were given an initial diagnosis of CD. The first referral from the general practitioner was to a specialist other than a neurologist in 31% of patients. Patients were seen by a mean of three doctors (range one to nine) before being given the correct diagnosis of CD. Delay to diagnosis of CD may in part be due to lack of awareness of the condition amongst health care professionals. Improved diagnostic skill appears likely to have had a substantial impact on the delivery of appropriate treatment in this population.